PENGEMBANGAN PETERNAKAN ITIK MAGELANG BERBASIS MASYARAKAT MANDIRI DI DESA NGADIROJO, KECAMATAN SECANG, KABUPATEN MAGELANG - Ayu Rahayu; Tri Puji Rahayu (Universitas Perjuangan Tasikmalaya, 2020)
Duck population in Magelang area, especially Ngadirojo Village, Secang Subdistrict has decreased. The total population of ducks in Secang District is 9,980 tails while the total duck population for 2015 in Magelang Regency according to the Department of Animal Husbandry and Fisheries of Magelang Regency is 186,736. The main problem of Ngadirojo Village, Secang Subdistrict is the origin of Magelang Ducks, but now the population is decreasing. The lack of knowledge of the community about the maintenance management of Magelang ducks is one of the causes of the reduced duck population in the village. So it is offered a solution that is solutive to overcome this problem, namely by growing the interest of farmers to want to raise ducks as a main and sideline business, especially for young people who have not worked, and increase the knowledge and skills of farmers about Magelang duck cultivation techniques. After that the expected output target is to produce skilled farmers in Magelang duck maintenance management and produce young entrepreneurs through Magelang duck. The method that is carried out is the holding of socialization and counseling regarding the maintenance management of Magelang Duck and its marketing.Keywords: Ngadirojo Village, Magelang Duck, Livestock DevelopmentÂ